Implikasi dan Arah Kebijakan Pemberian Anggaran APBN/APBD Untuk Operasional Pengelola Zakat dalam Meningkatkan Fungsi Pemerintah - Solihah, Cucu (Universitas Serang Raya, 2017)
The commitment in building Indonesia as a prosperous country gives consequence to the role of government in prospering the community. It is conducted by empowering the programs having potency of financial sources for developing this state. Beside the tax as the financial source of state development, the government enforces the policy of zakat management. The policy is the act number 23 in 2011 concerning zakat management in which the fund derives from the national / regional budget. In this case, the national or regional zakat council manages the zakat management. It is expected, it can help the process of state development and be a media in improving the social welfare as one of the government?s roles